"At this age, a Moroccan woman's life's work is over"-older Moroccan-Dutch migrant women's perceptions of health and lifestyle, with a focus on Ramadan experiences: qualitative research integrating education and consultation - Karlijn Koudstaal; Petra Verdonk; Edien Bartels (BMC, 2020)
Abstract Background Older Moroccan-Dutch migrant women exhibit high rates of diabetes, hypertension, overweight and obesity which is further compounded by their high risk of multi-morbidity. Healthcare professionals' efforts to encourage this group to adopt a healthier lifestyle have little success. We ask ourselves whether the concepts used in health education and promotion relate to these women's experiences and beliefs. Today's pluralistic Dutch society requires a more differentiated and applied approach, not in an essentialist way but in awareness that translation of rather individualized concepts like health and lifestyle is not always adequate, as the meaning and interpretation of such concepts may differ and may be related to women's other (fundamental) perceptions. This can have practical consequences for health promotion and education. The aim of this explorative, qualitative research, conducted between April and September 2015 and taking an intersectional approach, was to explore older Moroccan-Dutch women's perceptions of health and lifestyle and to analyse these in a broader context, related to other fundamental forms of identity such as gender, culture and religion. Methods We recruited women with Moroccan backgrounds by approaching Moroccan women's organisations and using the snowballing method (chain-referral sampling). Seven 'natural' group discussions were held (amongst women who regularly meet each other, aged between 22 and 69 years), and twelve in-depth interviews and an observation day (with women from 40 to 66 years). The transcripts were then analysed using thematic content analysis. Results Five major themes were identified. Health was perceived of in the terms used in prevailing health promotion discourses in the Netherlands, but lifestyle was interpreted in a much broader sense than the current health promotion debate allows; it is not seen as an individual responsibility or as something an individual could control on their own, and the social benefits of health behaviours appear to outweigh the health benefits themselves. Lifestyle was located in three main social identities of the women: Moroccan, Muslim and mother. Finally, Ramadan played a huge and dominant role in the lifestyle experience of older Moroccan women and was central in this research. Conclusions The finding that lifestyle is not seen as an individual responsibility but is located in social identities, can be applied to other settings that older migrant-Dutch women occupy. Further research will clarify this.